2023
DOI: 10.3389/fimmu.2023.1113385
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cuproptosis hub genes contributing to the immune microenvironment in ulcerative colitis using bioinformatic analysis and experimental verification

Abstract: InstructionUlcerative colitis (UC) can cause a variety of immune-mediated intestinal dysfunctions and is a significant model of inflammatory bowel disease (IBD). Colorectal cancer (CRC) mostly occurs in patients with ulcerative colitis. Cuproptosis is a type of procedural death that is associated with different types of diseases to various degrees.MethodsWe used a combination of bioinformatic prediction and experimental verification to study the correlation between copper poisoning and UC. We used the Gene Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…While apoptosis, pyroptosis, necroptosis, and autophagy have been extensively investigated in UC, [47][48][49] recent research has also explored the involvement of ferroptosis and cuproptosis in this condition. 50,51 However, there is limited research on the regulatory 52 Through bioinformatics and experimental verification, our study identified key genes related to PANoptosis and autophagy, potentially influencing immune dysregulation and wound healing in UC.…”
Section: Discussionmentioning
confidence: 97%
“…While apoptosis, pyroptosis, necroptosis, and autophagy have been extensively investigated in UC, [47][48][49] recent research has also explored the involvement of ferroptosis and cuproptosis in this condition. 50,51 However, there is limited research on the regulatory 52 Through bioinformatics and experimental verification, our study identified key genes related to PANoptosis and autophagy, potentially influencing immune dysregulation and wound healing in UC.…”
Section: Discussionmentioning
confidence: 97%
“…and Disul dptosis [43]. The roles of apoptosis, pyroptosis, necroptosis, and autophagy have been extensively investigated in UC [44][45][46], and recently there has been a growing body of research exploring the involvement of ferroptosis and cuproptosis in UC [47,48]. However, there are no bioinformatics-based studies or experimental researches to demonstrate the regulatory role of PANoptosis in UC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed notable changes for the levels of various classical programmed cell death pathways in UC intestinal epithelial cells (IECs) and intestinal mucosal immune cells, such as apoptosis, necrosis, and pyroptosis, which in turn lead to an imbalance of the intestinal mucosal barrier and immune homeostasis in patients with UC, and are an important influence on the development of UC (Supplementary Table S1 - S3 ) 2 , 3 . Ferroptosis and cuproptosis have been successively discovered as novel modes of programmed cell death in recent years 4 , 5 , and their roles and mechanisms in UC are being successively reported, further revealing the key regulatory roles of novel modes of programmed cell death in UC intestinal mucosal homeostasis 6 8 . Therefore, further exploration of the changes and regulatory mechanisms of various types of programmed cell death in UC intestinal mucosal tissues will be beneficial for further elucidating the pathogenesis of UC and finding new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%